The subject is objects - Zweben, Monte (Manufacturing systems, 1996)
Object-oriented software results from a kind of modular programming. Each object is a software package containing a collection of related procedures and data. Reuse of proven components shortens application development time. Objects make it easier to customize software systems to fit a company's business processes, and to do so without negatively impacting the ability to migrate to later software releases. The 2 defining features of an object-oriented approach are encapsulation and inheritance. Overuse of the term object can be linked to an incorrect definition of an object as any data record that has a collection of fields. Unfortunately, this does not capture the true power of objects. Objects certainly encapsulate data in their fields. More importantly, however, objects also encapsulate behavior. An object contains both data and a collection of procedures for manipulating those data. These procedures are called methods in object-oriented parlance. Inheritance, specialization, and the advantages of object-oriented software are discussed in detail.